Physical and Biological Determinants of the Fabrication of Molluscan Shell Microstructures - Checa, Antonio G. (Frontiers in Marine Science, 2018)
Molluscs are grand masters in the fabrication of shells, because these are composed of the largest variety of microstructures found among invertebrates. Molluscan microstructures are highly-ordered aggregates of either calcite or aragonite crystals with varied morphologies and three-dimensional arrangements. Classically, every aspect of the fabrication of microstructural aggregates is attributed to the action of proteins. There was, however, only direct evidence that the mineral phase, and indirect evidence that nucleation and the crystal shape, are determined by the types of soluble proteins. Some authors imply that crystal competition may also play a role. In addition, the fabrication of intergranular organic matrices typical of some microstructures (nacre, columnar prismatic) cannot have a protein-based explanation. Over the last decade I and collaborators have been applying a holistic view, based on analyzing and interpreting the features of both the organic (mantle, extrapallial space, periostracum, organic matrices) and inorganic (crystallite morphology, arrangement and crystallography) components of the biomineralization system. By interpreting them on biophysical principles, we have accumulated evidence that, in addition to the activity of proteins, other mechanisms contribute in an essential way to the organization of molluscan microstructures. In particular, we have identified processes such as: (1) crystal nucleation on preformed membranes, (2) nucleation and growth of crystals between and within self-organized membranes, (3) active subcellular processes of contact recognition and deposition. In summary, besides the activity of organic macromolecules, physical (crystal competition, self-organization) and /or biological (direct cellular activity) processes may operate in the fabrication of microstructures. The balance between the physical and biological varies among microstructures, with some being based exclusively on either physical or biological processes, and others having a mixed nature. Other calcifying invertebrates (e.g. corals, cirripeds, serpulids) secrete microstructures that are very similar to inorganic crystal aggregates, and only some brachiopods and, to a lesser extent, bryozoans may have secretory abilities comparable to those of molluscs. Here I provide a new perspective, which may allow microstructures to be understood in terms of evolutionary constraints, to compare the secretional abilities among taxa, and even to evaluate the probability of mimicking microstructures for the production of functional synthetic materials.